Impression management and non-GAAP disclosure in earnings announcements - Guillamon-Saorin, E.; Isidro, H.; Marques, A. (Journal of Business Finance and Accounting, 2017)
We study the market's reaction to the disclosure of non-GAAP earnings measures that are combined with high impression management. We construct an impression management score that captures several communication techniques that managers often use to positively bias investors’ perceptions of firm's performance. We hand-collect and code both quantitative and qualitative information from earnings announcement press releases of large European firms. Our results indicate that non-GAAP measures are informative to capital markets. However, non-GAAP adjustments are more persistent when accompanied by higher levels of impression management. This evidence is consistent with managers attempting to distort users’ perceptions when non-GAAP adjustments are of lower quality. Market reaction tests suggest that investors are able to see through managers’ intentions and discount non-GAAP information that is accompanied by high impression management. Moreover, investors in more sophisticated markets penalize non-GAAP measures communicated with high impression management. Our results are robust to a battery of sensitivity tests, including using a machine-coded tone measure